-(1-7x)-6(-7-x)=36

Simple and best practice solution for -(1-7x)-6(-7-x)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(1-7x)-6(-7-x)=36 equation:


Simplifying
-1(1 + -7x) + -6(-7 + -1x) = 36
(1 * -1 + -7x * -1) + -6(-7 + -1x) = 36
(-1 + 7x) + -6(-7 + -1x) = 36
-1 + 7x + (-7 * -6 + -1x * -6) = 36
-1 + 7x + (42 + 6x) = 36

Reorder the terms:
-1 + 42 + 7x + 6x = 36

Combine like terms: -1 + 42 = 41
41 + 7x + 6x = 36

Combine like terms: 7x + 6x = 13x
41 + 13x = 36

Solving
41 + 13x = 36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-41' to each side of the equation.
41 + -41 + 13x = 36 + -41

Combine like terms: 41 + -41 = 0
0 + 13x = 36 + -41
13x = 36 + -41

Combine like terms: 36 + -41 = -5
13x = -5

Divide each side by '13'.
x = -0.3846153846

Simplifying
x = -0.3846153846

See similar equations:

| 7x+35=-21 | | 13+2d+4d+3d+9= | | -16b=9 | | y=x^2-6x-3 | | 26+b=20 | | -8x-9x=.66 | | 2a=18 | | 12=x^2-6x | | 3x+9-x=15 | | 36x^2-9x=0 | | 10x^2-8x+1=0 | | 10x^2=58 | | 19x^2=58 | | 24a-22=-49(1-6a) | | 3x+11=-1 | | 16x-3=102-5x | | 107-14-6y=-2(y-4y) | | 60-2x+70-4x=180 | | 4/5/10/6= | | h=3+65t-16t^2 | | h=-16t^2+65t+3 | | -35=-7(5p-5)-5(4p+3) | | -52=-8(4-5n)-4(n-4) | | -1+x^2-1x=0 | | 4(-7+2m)+4(1-m)=-36 | | (80-x)+(90-2x)=180 | | x^2-x=23 | | 79=-5(2x+3)-7(-4+8x) | | 12x+13=56 | | 12+x(13)=12 | | 6(3x-8)=14x-20 | | 3z^2-13z+4=0 |

Equations solver categories